ON NECESSARY OPTIMALITY CONDITIONS FOR RAMSEY-TYPE PROBLEMS - Anton O. Belyakov (Ural Mathematical Journal)
We study an optimal control problem in infinite time, where the integrand does not depend explicitly on the state variable. A special case of such problem is the Ramsey optimal capital accumulation in centralized economy. To complete the optimality conditions of Pontryagin's maximum principle, so called transversality conditions of different types are used in the literature. Here, instead of a transversality condition, an additional maximum condition is considered.